Nasopharyngeal Cancer in Kano – A Histo Pathologic Review - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Nasopharyngeal cancer (NPC) represents the most common head and neck malignancy in most Nigerian centers. Although it is uncommon among all cancers, it has significant morbidity and mortality associated with it. There has been no specific study on NPC in our locality. This review, therefore, endeavors to document and evaluate the pattern in our center.Materials and Methods:This was a retrospective review of all nasopharyngeal cases diagnosed at the pathology department of our hospital between 1stJanuary 2005 and 31stDecember 2014. The biodata and histopathological findings were reviewed.Results:NPC accounted for 1.3% of all cancers during the study period and was twice as common in males than females (M: F = 2.1:1). Patients’ age ranged from 16 to 70 years with median of 38 years and bimodal peaks in the 3rdand 5thdecades. Squamous carcinoma was the most frequent histologic type (97.1%), followed by adenoid cystic and papillary adenocarcinoma each comprising 1.4%. The prevalent squamous carcinoma subtypes were non-keratinizing (80%) and keratinizing (17%).Conclusion:Our findings were broadly similar to other Nigerian centers, but slightly at variance with other low incidence zones in Western world.